Meeting health standards for export - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Dr David Ikiror, an animal health scientist working in Kenya describes the basic principles of good livestock health and argues t hat livestock farmers must become more market oriented.